Analisis Harga Pokok Produksi Menggunakan Metode Full Costing Pada CV Cielofood Pratama - Agung Laksono; Tri Koko Apanugra; Akbar Anggisa; Yuni Astuti Tri Tartiani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The analysis of production costs using the full costing method at CV Cielofood Pratama in Bogor aims to set accurate selling prices through comprehensive production cost calculations. This study applied a descriptive case study approach, utilizing primary data from observations and interviews as well as secondary data. The analysis revealed a total monthly production cost of Rp 42,200,000, with a per-unit cost of Rp 15,461.54. These results demonstrate that the full costing method provides a complete overview of all production expenses, aiding management in decision-making related to pricing strategies and operational efficiency. The practical implication of this method can enhance the company's competitiveness in the market.